2015
DOI: 10.1016/j.conb.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensation in Drosophila

Abstract: Animals use thermosensory systems to achieve optimal temperatures for growth and reproduction and to avoid damaging extremes. Thermoregulation is particularly challenging for small animals like the fruit fly Drosophila melanogaster, whose body temperature rapidly changes in response to environmental temperature fluctuation. Recent work has uncovered some of the key molecules mediating fly thermosensation, including the Transient Receptor Potential (TRP) channels TRPA1 and Painless, and the Gustatory Receptor G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 52 publications
2
103
0
Order By: Relevance
“…melanogaster, three channels belonging to the TRPA subfamily are related to thermosensation (dTRPA1, painless and pyrexia) and mediate responses to moderate and high temperatures (Dhaka et al, 2006;Hamada et al, 2008;Barbagallo and Garrity, 2015), fact that has also been observed recently in other insect species (Kim et al 2015). painless and pyrexia channels are present in other insect species (like Bombyx mori, Tribolium castaneum, Apis mellifera, Nasonia vitripennis and Pediculus humanus), suggesting that channels for the detection of noxious temperatures are conserved among different insect taxa (Matsuura et al, 2009).…”
Section: Introductionmentioning
confidence: 66%
“…melanogaster, three channels belonging to the TRPA subfamily are related to thermosensation (dTRPA1, painless and pyrexia) and mediate responses to moderate and high temperatures (Dhaka et al, 2006;Hamada et al, 2008;Barbagallo and Garrity, 2015), fact that has also been observed recently in other insect species (Kim et al 2015). painless and pyrexia channels are present in other insect species (like Bombyx mori, Tribolium castaneum, Apis mellifera, Nasonia vitripennis and Pediculus humanus), suggesting that channels for the detection of noxious temperatures are conserved among different insect taxa (Matsuura et al, 2009).…”
Section: Introductionmentioning
confidence: 66%
“…A number of Trps are expressed in taste and olfactory organs of the fly [7, 85]. Two of them, TrpA1 and Painless, act in thermosensation [126] but are also expressed in taste organs. TRPA1 is required for the response to noxious electrophiles, and is activated by electrophiles when expressed in Xenopus oocytes [127].…”
Section: Figmentioning
confidence: 99%
“…36,37) Drosophila have four TRPA channels-TRPA1, Painless (Pain), Pyrexia (Pyx) and water witch (Wtrw). With the exception of Wtrw all of these are involved in thermosensation.…”
Section: Trpamentioning
confidence: 99%
“…Although TRPA1 is involved in the noxious heat response, this response also involves the other two thermoTRPs-Pain, which has a temperature activation threshold of 39 to 42°C, and Pyx, which opens at 46°C, but the individual roles of the three channels are unclear. 13,36) TRPA1 is likewise required for avoidance of high-intensity light by larvae, by an unknown mechanism that may also involve a gustatory receptor.…”
Section: Trpamentioning
confidence: 99%